Macrosomia and Related Adverse Pregnancy Outcomes: The Role of Maternal Obesity - Gaudet, Laura (Université d'Ottawa / University of Ottawa, 2012)
Fetal overgrowth is associated with adverse outcomes for offspring and with maternal obesity. Results from a systematic review and meta-analysis showed that maternal obesity is associated with fetal overgrowth, defined as birthweight ≥4000g (OR 2.17, 95% CI 1.92, 2.45), birthweight ≥4500g (OR 2.77, 95% CI 2.22, 3.45) and birthweight ≥90%ile for gestational age (OR 2.42, 95% CI 2.16, 2.72). A retrospective cohort study revealed that mothers whose infants are macrosomic are more likely to require induction of labour (OR 1.42, 95% CI 1.10-1.98) and delivery by Cesarean section (OR 1.45, 95% CI 1.04-2.01), particularly for maternal indications (OR 3.7, 95% CI 1.47-9.34), if they are obese. Infants from these pregnancies are significantly more likely to require neonatal resuscitation in the form of free flow oxygen (OR 1.57, 95% CI 1.03, 2.42) than macrosomic infants of non-obese mothers. Thus, co-existing maternal obesity and macrosomia increases the risk of adverse pregnancy outcomes.
Keywords: Macrosomia; Obesity; Pregnancy; Pregnancy Outcomes